PENGARUH PERKEMBANGAN PEMBANGUNAN INFRASTRUKTUR JALAN TERHADAP PERTUMBUHAN PEMANFAATAN LAHAN KOTA - Ida Susanti (UNIVERSITAS LAMPUNG, 2013)
The road infrastructure has a significant influence on the development facilities of the city as acenter of a new generation. Bandar Lampung as the capital of Lampung province was not im -mune to these problems. Development of a very dynamic with a diverse urban population, trig-gered over the land due to the complexity of the construction of roads that will lead to many nega-tive issues in the future. Problem caused by the increasing development of road infrastructure inand on the outskirts of the city, will increase the rate of population growth to the high impact ofurban land usage that is not in line with the regional spatial plan. To suppress the effect of infra-structure development on land conversion, required policy analysis tool. The making of policysimulation modeling of land usage on the development of road infrastructure using dynamic sys-tem modeling. The models created using causality approach (causal loop), starting from the basicmodeling that is a mapping of the real system of urban land usage which is then converted into 4model. Model of transportation, demography, population and land usage activities, which are as-sociated with a causal relationship. The models will be aided by the GIS as spatial data analysisinput, the models simulate some policy scenarios. The most optimal scenario results to reducingthe rate of population growth, reduce the level of unemployment, increased GDP, and control thepattern of land usage. By performing simulations using these scenarios, all the desired purposecan be met and brought a good impact on the growth of Bandar Lampung city.